Knowing to care: characterization of individuals with spinal cord injury treated at a rehabilitation center - Soraia Dornelles Schoeller; Andréa Regina Schuch Grumann; Alessandra Cadete Martini; Stefânia Forner; Lívia Takano Sader; Giovani Cavalheiro Nogueira
Introduction Spinal cord injury (SCI) results in motor, sensory and autonomic dysfunction. The symptoms observed in patients with spinal cord injury will depend on the area affected by the injury. Nursing care is essential for better patient outcomes. Objective The aim of this study was to characterize patients with spinal cord injury treated at a state referral rehabilitation center for SCI. Methods We performed a quantitative cross-sectional descriptive study of 109 patients between the years 2000 and 2009. Results We found a predominance of spinal cord injury in men aged up to 30 years (48.5%). The main causes of spinal cord injuries were traffic accidents. The thoracic region was the most frequently affected site (39.7%), followed by the cervical region (25.6%). Most of the study subjects had been rated as ASIA A, according to the American Spinal Cord Injury Association scale. Discussion These findings corroborate previous studies observing that traffic accidents are the leading causes of spinal cord injury and that people affected by it usually do not seek proper care. Receiving early intervention services and counseling is essential for a better outcome and for achieving an improvement in the quality of life of these patients. Conclusion Despite the increasing incidence of spinal cord injuries nowadays, there is still a lack of data on the subject. The greatest limitation of this study is the incompleteness of medical records, which hindered the access to information.